„Zbiór ten nie zostanie bezużytecznym w księgarstwie ciężarem…”, czyli Narodowe Pieśni Serbskie wybrane i przełożone przez Romana Zmorskiego - Lis-Wielgosz, Izabela (Przekłady Literatur Słowiańskich, 2016)
“This collection will not be a useless burden for the book trade” that is, Serbian folk Songs selected and translated by Roman Zmorski In the article, the collection of Serbian folklore song translations, entitled Serbian Folk Songs, is regarded. The collection itself was prepared and published in 1853 and 1855 by Roman Zmorski. Located in the centre of consideration, it also becomes a pretext for a reflection on the essence of a literary text’s translation along with its communicational aspect and the role of the translator in the process of the fusion concerning two axiological systems, two cultural horizons — the initial one and the final one. Furthermore, the article serves to present a traditional translation in the nineteenth century: the reception of South Slavonic (Serbian) folklore poetry. The considerations dedicated to the translation theme and the translator’s role concentrate not on the philological issues themselves, but rather on the broadly comprehended intercultural phenomenon which means a process and the result of a transposition of the text from one cultural realm to the other. Besides the exposition of the translation meaning in the relational, dialogical aspect, its fundamental conditions are emphasized. They refer to the historical and cultural contexts, sources’ selection, and intentional operation on the primary text together with its translation understood as a specific sort of interpretation and communication. Key words: Serbian folklore songs, folklore poetry, translations, translator, reception, collection